If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(u + 4) = -3u + -16 Reorder the terms: -7(4 + u) = -3u + -16 (4 * -7 + u * -7) = -3u + -16 (-28 + -7u) = -3u + -16 Reorder the terms: -28 + -7u = -16 + -3u Solving -28 + -7u = -16 + -3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3u' to each side of the equation. -28 + -7u + 3u = -16 + -3u + 3u Combine like terms: -7u + 3u = -4u -28 + -4u = -16 + -3u + 3u Combine like terms: -3u + 3u = 0 -28 + -4u = -16 + 0 -28 + -4u = -16 Add '28' to each side of the equation. -28 + 28 + -4u = -16 + 28 Combine like terms: -28 + 28 = 0 0 + -4u = -16 + 28 -4u = -16 + 28 Combine like terms: -16 + 28 = 12 -4u = 12 Divide each side by '-4'. u = -3 Simplifying u = -3
| 3x+x=y-18 | | 9x+4x+2=8x+3+4x | | -9=-6+x | | .10(8-x)+x=0.40(8) | | 12-2t=1-t | | -9=32x | | (4y+5)(6y-1)= | | 32-6x=12 | | 8v+2=12+3v | | 32-10x=12 | | 4(3x+6)=8(-6x-3) | | 0.45(19-x)+x=0.40(19) | | 3x^2+7x-28=2x^2-7x+4 | | 2t=5t-45 | | 4x+20=14x+-70 | | -21=-3x-4x | | 4x+10=14x-70 | | A+10=-30 | | 10+-8x=3x-12 | | Y=35000+750x | | 5(2x-6)-5=5(x-5)+35 | | -13=1+6x+8x | | x^3+7x-4=0 | | f*2-15f+36=0 | | 10x-6=6x+18 | | (m-1)x^2-(2m-1)x+(m-1)=0 | | Y=750x+35000 | | 4(x+6)-2x=x+15 | | 10=3(-x+4) | | b-8+4b=28 | | 553= | | 8(6n+1)+4n=424 |